Aluminum surface coating of copper using highcurrent electron beam - Donets, S.E.; Klepikov, V.F.; Lytvynenko, V.V.; Lonin, Yu.F.; Ponomarev, A.G.; Starovoytov, R.I.; Startsev, O.A.; Uvarov, V.T. (Вопросы атомной науки и техники, 2015)
High-current electron beam irradiation has been applied for surface coating of copper with aluminum in ablative mode at the TEMP-A accelerator with energy of 350 keV, pulse length of 5 μs, and fluence 10…200 J/cm2. The aluminum-rich surface layer with average thickness around 25 μm, microhardness of 6.7 GPa and elasticity modulus of 122 GPa was formed on the copper template.